Frailty assessment in an unselected population admitted to an intensive cardiac care unit. (14th October 2021) - Campanile, A; Procaccini, C; Dell' Aquila, F; Tedeschi, M; Rispoli, A; Sorrentino, R; Ravera, A
Abstract: Background: Although interest in frailty has expanded among cardiology experts over the past 2 decades, its integration, as part of cardiovascular disease management, is still lacking, above all in the acute cardiac care setting. The Clinical Frailty Scale (CFS) is a brief guided tool to assess frailty in hospital settings without specialist equipment. Purpose: Our objective was to test the performance of the CFS in an older, unselected population, admitted to an Intensive Cardiac Care Unit (ICCU) during the year 2019. Methods: The study sample included 431 patients ≥65 years old, admitted to an ICCU of a tertiary cardiac center in Italy. The CFS ranged from "very fit: 1" to "terminally ill: 9", but it was considered present at a score ≥5. Our primary endpoint was defined by a combination of severe complications requiring critical care and in-hospital death. The data were collected from the hospital discharge summary and the electronic chart records. Results: 158 patients (36.7%) were frail. These individuals had greater comorbidity and higher in-hospital mortality (Table 1). After a multivariable logistic regression analysis, 4 predictors were identified: signs of congestive heart failure (OR: 8.51, 95% Confidence Interval-CI: 4.63–14.6; p<0, 001), systolic blood pressure (OR per 1 mmHg increasing: 0.98, 95% CI: 0.97–0.99; p<0, 001), smoking habit (OR: 0.49, 95% CI: 0.22–1.11; p=0.09) and the CFS ≥5 (OR: 1.86, 95% CI: 1.08–3.23: p=0, 026). Conclusions: The CFS is a simple guided frailty tool that may enhance outcome prediction in the acute cardiac care setting. These findings merit evaluation in larger cohorts of unselected patients. FUNDunding Acknowledgement: Type of funding sources: None.